Erythropoietin concentration in acute kidney injury is associated with insulin‐like growth factor‐binding protein‐1. Issue 8 (19th July 2016) - Yamashita, Tetsushi; Noiri, Eisei; Hamasaki, Yoshifumi; Matsubara, Takehiro; Ishii, Takeshi; Yahagi, Naoki; Nangaku, Masaomi; Doi, Kent
Abstract: Aim: Erythropoietin (EPO) production is stimulated by hypoxia in the kidney. Ischaemic injury plays a crucial role in the pathogenesis of acute kidney injury (AKI). However, EPO concentrations in critically ill patients complicated with AKI have not been evaluated sufficiently. This study was conducted to clarify the factors associated with plasma EPO concentrations in AKI. Methods: This study prospectively enrolled 98 critically ill adult patients treated at the adult mixed ICU. Plasma EPO, insulin‐like growth factor‐binding protein‐1 (IGFBP‐1), neutrophil gelatinase‐associated lipocalin (NGAL), interleukin‐6 (IL‐6) and urinary N‐acetyl‐β‐D‐glucosaminidase (NAG) were measured on ICU admission. Results: Acute kidney injury occurred in 42 (42.9%) patients. Significantly higher plasma EPO in the AKI group was detected than in the non‐AKI group (16.13 (9.87–28.47) mIU/mL versus 27.81 (10.16–106.02) mIU/mL, P < 0.05). Plasma IGFBP‐1 in the AKI group was also significantly higher than in the non‐AKI group (19 208 (8820–50 780) pg/mL versus 63 199 (25 289–147 489) pg/mL, P < 0.05). Plasma EPO concentration was negatively correlated with haemoglobin in the non‐AKI group with statistical significance, but not in the AKI group. Multiple logistic regression analysis revealed that plasma EPO in the AKI group was associated significantly with plasma IGFBP‐1 and complication of diabetes mellitus, but not the haemoglobin concentration, partial pressure of arterial oxygen (PaO2 ), and IL‐6. Conclusions: Not low arterial oxygen tension, haemoglobin concentration, and inflammation evaluated by IL‐6 but plasma IGFBP‐1 was significantly associated with plasma EPO concentration in AKI, suggesting an unknown mechanism related to systemic stress conditions for EPO regulation in AKI. Summary at a Glance: This study by Yamashita et al investigated the association of plasma EPO concentrations with plasma IGFBP‐1, diabetes complications and systemic inflammation in AKI patients. They found that increased EPO concentrations in AKI patients are associated with high plasma IGFBP‐1and complication of diabetes mellitus, but not IL‐6. The authors addressed all the questions raised by two reviewers. The revised manuscript is generally well written and clearly presented.